Hypomethylation of the cyclin D1 promoter in hepatitis B virus-associated hepatocellular carcinoma. Issue 20 (15th May 2020) - Liu, Hui-Hui; Fang, Yu; Wang, Jing-Wen; Yuan, Xiao-Dong; Fan, Yu-Chen; Gao, Shuai; Han, Li-Yan; Wang, Kai
Abstract : Abstract: The hypomethylation of the Cyclin D1 ( CCND1 ) promoter induced by excess oxidative stress likely promotes the development of hepatitis B virus-associated hepatocellular carcinoma (HBV-HCC). We aimed to evaluate methylation status of the CCND1 promoter as a new plasma marker for the detection of HBV-HCC. We consecutively recruited 191 participants, including 105 patients with HBV-HCC, 54 patients with chronic hepatitis B (CHB), and 32 healthy controls (HCs). Using methylation-specific polymerase chain reaction, we identified the methylation status of the CCND1 promoter in plasma samples. We analyzed the expression levels of the CCND1 mRNA in peripheral blood mononuclear cells by using quantitative real-time PCR. We assessed the plasma levels of superoxide dismutase, 8-hydroxydeoxyguanosine and malondialdehyde by using enzyme-linked immunosorbent assays. Patients with HBV-HCC (23.81%) presented a reduced methylation frequency compared with patients with CHB (64.81%) or HCs (78.13%) ( P  < .001). When receiver operating characteristic curves were plotted for patients with HBV-HCC versus CHB, the methylation status of the CCND1 promoter yielded diagnostic parameter values for the area under the curve of 0.705, sensitivity of 76.19%, and specificity of 64.81%, thus outperforming serum alpha-fetoprotein (AFP), which had an area under the curve of 0.531, sensitivity of 36.19%, and specificity of 90.74%. Methylation of the CCND1 promoter represents a prospective diagnostic marker for patients with AFP-negative HBV-HCC and AFP-positive CHB. The expression levels of CCND1 mRNA was increased in patients with HBV-HCC compared with patients with CHB (Z = -4.946, P  < .001) and HCs (Z = -6.819, P  < .001). Both the extent of oxidative injury and antioxidant capacity indicated by the superoxide dismutase, 8-hydroxydeoxyguanosine and malondialdehyde levels were increased in patients with HBV-HCC. Clinical follow up of patients with HBV-HCC revealed a worse overall survival ( P  = .012, log-rank test) and a decreased progression-free survival (HR = 0.109, 95%CI: 0.031-0.384) for the unmethylated CCND1 group than methylated CCND1 group. Our study confirms that oxidative stress appears to correlate with plasma levels of CCND1 promoter methylation, and the methylation status of the CCND1 promoter represents a prospective biomarker with better diagnostic performance than serum AFP levels.